Correction to: prediction accuracy improvement for Bitcoin market prices based on symmetric volatility information using artificial neural network approach (Journal of Revenue and Pricing Management, (2020), 10.1057/s41272-020-00229-3) - Othman, Anwar Hasan Abdullah; Kassim, Salina; Rosman, Romzie; Redzuan, Nur Harena (Palgrave Macmillan Ltd., 2020)
The original version of this article unfortunately contained a mistake. Prediction accuracy percentage in Fig. 7, which represent the key findings of this study which is (92.147%) does not appear in Fig. 7. The corrected Fig. 7 with caption is given below.